Effects of patulin on rumen microbial fermentation in continuous culture fermenters - Tapia, Maria Ofelia (2002)
Eight single-flow continuous culture fermenters were used to study the effects of different concentrations of patulin on rumen microbial fermentation. Two 1 l fermenters were spiked with 0, 30, 60 or 90 mg of patulin every 12 h for 3 consecutive days. True digestion of organic matter (TOM), acid detergent fiber (ADF) and crude protein (CP) decreased (P<0.05, P<0.01 and P<0.01, respectively) with patulin addition ranging from 30 to 90 mg. Bacterial nitrogen flow was lower (P<0.01) with patulin addition (30–90 mg) compared with the control treatment, whereas, the efficiency of bacterial growth (g of N/kg OMTD) was lowest (P<0.05) when 90 mg of patulin were added to fermenter flasks. Total volatile fatty acid (VFA) concentration (mM) in fermenter effluents decreased (P<0.05) from 180.1 to 119.5 with the addition of 90 mg of patulin but did not differ (P>0.05) between the control treatment and 30–60 mg of patulin. Acetate (mol/100 mol) was depressed (P<0.01) with patulin addition. Conversely, there was an increase (P<0.05) in the molar proportion of butyrate and valerate in the fermenters treated with the toxin. At the highest level of patulin addition (60 and 90 mg), branched-chain VFA were lower (P<0.01) probably due to a reduction in protein (branched-chain amino acid) degradation. It is concluded that patulin can alter metabolism of nutrients by ruminal microbes. These changes could potentially have a negative impact on animal health and performance.